ANALISIS DAMPAK LITERASI KEUANGAN, OVERCONFIDENCE, DAN MOTIVASI TERHADAP KEPUTUSAN INVESTASI - Rendi Wiliam Dahata (2023)
This study aims to examine the effect of financial literacy, overconfidence, and motivation on investment decisions. In this study, a quantitative method was used with a population of individual investors who live in Jakarta. The sampling method used is non-probability sampling, namely accidental sampling. Respondents who were successfully collected were 133 respondents. Hypothesis testing will use SmartPLS 3 software with partial least square techniques. The test results concluded that the three variables namely financial literacy, overconfidence, and motivation have a positive effect on investment decisions.